1972
DOI: 10.3171/jns.1972.37.3.0316
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow following induced subarachnoid hemorrhage in the monkey

Abstract: ✓ The acute effects of experimental subarachnoid hemorrhage on cerebral blood flow were investigated in 14 adult rhesus monkeys injected with fresh autogenous blood through a needle positioned within the subfrontal subarachnoid space. Cerebral blood flow was measured by the xenon133 tissue clearance method before hemorrhage, and afterward at 30-minute intervals for a 3-hour period. Post-anesthetic neurological status was graded according to Botterell's classification. Twelve monkeys showed a significant decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
3
3

Year Published

1975
1975
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 28 publications
1
6
3
3
Order By: Relevance
“…87 " 40 Despite these reports the lack of effect of intra-arterially administered 5-HT, reported here and by other workers, 8 ' •• 8S suggests that the major cerebral blood flow changes described in migraine 41 -42 and subarachnoid hemorrhage 48 - 44 cannot be attributed to 5-HT arriving on the endothelial side of the receptor. This possibility may be accounted for by the rapid removal of 5-HT by uptake mechanisms and metabolism within the endothelial cell by monoamine oxidase.…”
Section: Deshmuck and Harpercontrasting
confidence: 48%
“…87 " 40 Despite these reports the lack of effect of intra-arterially administered 5-HT, reported here and by other workers, 8 ' •• 8S suggests that the major cerebral blood flow changes described in migraine 41 -42 and subarachnoid hemorrhage 48 - 44 cannot be attributed to 5-HT arriving on the endothelial side of the receptor. This possibility may be accounted for by the rapid removal of 5-HT by uptake mechanisms and metabolism within the endothelial cell by monoamine oxidase.…”
Section: Deshmuck and Harpercontrasting
confidence: 48%
“…Although their methods were quite like ours in most important respects, their results were significantly different in that they noted a significant fall in CBF immediately after SAH, which persisted until the experiment ended three hours later. The difference between the results of Petruk et al 42 and ours may be explained by the manner in which blood was injected into the chiasmatic cistern to produce the SAH. Petruk et al 42 injected 4 ml of blood within 20 seconds.…”
Section: Martins Doyle Newby Kobrine Ramirezcontrasting
confidence: 53%
“…The difference between the results of Petruk et al 42 and ours may be explained by the manner in which blood was injected into the chiasmatic cistern to produce the SAH. Petruk et al 42 injected 4 ml of blood within 20 seconds. We found that this rapid a rate of injection would often increase the ICP to a level that would transiently surpass the mean arterial blood pressure.…”
Section: Martins Doyle Newby Kobrine Ramirezcontrasting
confidence: 53%
See 1 more Smart Citation
“…Initial studies of this model have demon-strated that the rat experiences an acute global de crease of CBF following experimental SAH. These effects have been observed in other animal species (Hashi et al, 1972;Kamiya et al, 1983;Petruk et al, 1972;Umansky et al, 1983;Kuwayama et aI., 1972;Simeone et al, 1972;Varsos et al, 1983;Wilkins, 1980) as well as in humans (Ferguson et al, 1972;Granowska et al, 1980;Grubb et al, 1977;Ishii, 1979;James, 1968;Meyer et al, 1983;Voldby et al, 1985a), indicating that the rat may have similar circulatory responses to SAH.…”
mentioning
confidence: 80%